ANALYSIS OF ORGANIC MATTER AND PHYTOPLANKTON ABUNDANCE IN THE SUNGAI GUNTUNG ESTUARY WATERS, KATEMAN SUB-DISTRICT, INDRAGIRI HILIR REGENCY, RIAU PROVINCE - Nizar Rofiki; Bintal Amin; Sofyan Husein Siregar (Berkala Perikanan Terubuk, 2019)
This research was conducted in April to Mei 2019 to determine the content of organic matter and abundance of phytoplankton, to find out differences in organic matter and phytoplankton abundance between station and to know the relationship between organic matter content and phytoplankton abundance as reference for determining the condition of the Sungai Guntung estuary, Kateman Sub-district, Indragiri Hilir Regency, Riau Province. The method used in this study is  survey method, where the sampling locations consists of 4 research stations and each station consists of 3 sampling points. The results showed that organic matter content at station 1 had an average of 11.60 mg/l, station2 8.64 mg/l. Station 3 8.22 mg/l and station 4 8.22 mg/l. Phytopkankton species that found at Sungai Guntung estuary water is 21 species the Isthmia sp, Biddulphia sp, Chaetoceros sp, Rhizosolenia sp, Skeletonema sp, Thalassionema sp, Pleurosigma sp, Nitzschia sp, Synedra sp, Grammatophora sp, Thallassiothrix sp, Fragilaria sp, Navicula sp, Melosira sp, Asterionella sp, Cocconeis sp, Coscinodiscus sp, Stephanopyxis sp, Cyclotella sp, Bacteriastrum sp dan Oscillatoria sp. The highest abundance is in areas far from human settlements and around mangrove ecosystem, while the lowest abundance is in area near residential settlements and ports. Simple linear regression relationship between organic matter and the abundance of phytoplankton in Sungai Guntung estuary has a moderate relationship, where the correlation coefficient (r) = 0.36. The relationship between organic matter and phytoplankton abundance is negative, the higher the value of organic matter, the lower the abundance of phytoplankton..